Mechanistic study of filler dispersion enhancement in rubbers with environmentally safe processing oils - Iman Abbasi Shahdehi; Mohammad Abbasi-Soureshjani; Mohammad Alimardani (Results in Engineering)
The adoption of environmentally safer oils, such as TDAE (Treated Distillate Aromatic Extract), in rubbers has traditionally been approached with caution due to concerns over potential deterioration in filler dispersion and adverse impacts on mechanical performance. The present study systematically investigates the underlying mechanisms governing filler dispersion and presents robust evidence that replacing DAE (Distillate Aromatic Extract) with TDAE enhances the state of filler dispersion. Specifically, the effect of processing oils with varying aromatic content—DAE and TDAE—on filler network dynamics in Styrene-Butadiene Rubber (SBR) compounds was explored. Three oil loadings (10, 20, and 30 phr) were evaluated to assess their influence on carbon black dispersion and the resulting mechanical and viscoelastic properties. A bi-exponential kinetic model was employed to quantify both fast and slow flocculation processes during network formation. The results reveal that flocculation behavior is strongly dependent on both temperature and oil loading. TDAE, characterized by lower aromatic content, polarity, and viscosity, promotes superior filler dispersion, particularly at higher oil loadings and reduced processing temperatures, leading to enhanced microstructural uniformity and suppressed flocculation. In contrast, while DAE provides better dispersion at lower oil contents and at high temperatures, it exhibits significant filler agglomeration at higher loadings or near-ambient temperatures. Upon cooling, the lower compatibility of TDAE facilitates its faster migration out of the polymer inter-chain regions, leading to oil depletion near the polymer chains and the formation of loosely bound rubber, which increases inter-particle distances and disrupts filler-filler networking.